Relaxation-weighted MRI analysis of biofilm EPS: Differentiating biopolymers, cells, and water - Matthew R. Willett; Sarah L. Codd; Joseph D. Seymour; Catherine M. Kirkland (Biofilm)
Biofilms are a highly complex community of microorganisms embedded in a protective extracellular polymeric substance (EPS). Successful biofilm control requires a variety of approaches to better understand the structure-function relationship of the EPS matrix. Magnetic resonance imaging (MRI) is a versatile tool which can measure spatial structure, diffusion, and flow velocities in three dimensions and in situ. It is well-suited to characterize biofilms under natural conditions and at different length scales. MRI contrast is dictated by T1 and T2 relaxation times which vary spatially depending on the local chemical and physical environment of the sample. Previous studies have demonstrated that MRI can provide important insights into the internal structure of biofilms, but the contribution of major biofilm components—such as proteins, polysaccharides, and cells—to MRI contrast is not fully understood. This study explores how these components affect contrast in T1-and T2-weighted MRI by analyzing artificial biofilms with well-defined properties modeled after aerobic granular sludge (AGS), compact spherical biofilm aggregates used in wastewater treatment. MRI of these biofilm models showed that certain gel-forming polysaccharides are a major source of T2 contrast, while other polysaccharides show minimal contrast. Proteins were found to reduce T2 contrast slightly when combined with polysaccharides, while cells had a negligible impact on T2 but showed T1 contrast. Patterns observed in the model biofilms served as a reference for examining T2 and T1-weighted contrast in the void spaces of two distinct AGS granules, allowing for a qualitative evaluation of the EPS components which may be present. Further insights provided by MRI may help improve understanding of the biofilm matrix and guide how to better manage biofilms in wastewater, clinical, and industrial settings.